Whose News? The Media and Women's Issues - Joseph,Ammu and Sharma,Kalpana.ed (Sage, 1997)
Whose News?: The Media and Women’s Issues (1994) quickly became an international classic which was widely used. The decade that has passed since its publication has witnessed dramatic developments in the media environment across the world. As a consequence, the coverage of gender issues in the media today has to be viewed and evaluated against the background of globalization in general and media globalization in particular. This is just what this new and updated edition of the pioneering book does. In particular, it addresses the set of questions that has arisen in recent years concerning women’s access to the media and to information as users, their participation in media and communication structures, and their portrayal and perspectives in media content. This new edition retains its unique gender analysis of media content, and situates, views and evaluates the coverage of gender issues in the media within the context of recent trends in both the economy and the media industry. Employing a novel and nuanced methodology, it offers a distinctive view of the history of both the media and the women’s movement in India as the 20th century gave way to the 21st. It also examines current media coverage of women’s issues such as dowry-related violence, rape, sex selection, Muslim women’s legal rights, and the practice of sati.